An endogenous explanation of growth: direct-to-consumer stem cell therapies in PR China, India and the USA. (21st August 2018) - Datta, Saheli
The recent expansion of direct-to-consumer stem cell therapies (DSCTs) across nations where medical malpractice laws are the strongest globally challenges the causal assumption that low regulatory standards in developing countries bolster DSCTs. Drawing on firm-level data of existing biopharmaceuticals, approved stem cell therapies (SCTs) and DSCT clinics across the USA, PR China and India, this paper provides an innovation studies perspective of the ways in which the paradigmatic shift in fundamental knowledge production – from in vitro to in vivo stem cells – is transforming SCT discovery and delivery. It argues that the endogenous and inherent disruptive attributes of SCTs, rather than exogenous conditions like regulations, provide a substantive explanation for the recent expansion of DSCTs and urges regulatory adaptation to endogenous imperatives for effective governance of SCTs.